Succinylation and redox status in cancer cells - Dai, Xiaofeng; Zhou, Yanyan; Han, Fei; Li, Jitian (Frontiers in Oncology, 2022)
Succinylation is a post-translational modification (PTM) event that associates metabolic reprogramming with various pathological disorders including cancers via transferring a succinyl group to a residue of the target protein in an enzymic or non-enzymic manner. With our incremental knowledge on the roles of PTM played in tumor initiation and progression, relatively little has been focused on succinylation and its clinical implications. By delineating the associations of succinylation with cancer hallmarks, we identify the, in general, promotive roles of succinylation in manifesting cancer hallmarks, and conceptualize two working modes of succinylation in driving oncogenic signaling, i.e., via altering the structure and charge of target proteins towards enhanced stability and activity. We also characterize succinylation as a reflection of cellular redox homeostatic status and metabolic state, and bring forth the possible use of hyper-succinylated genome for early cancer diagnosis or disease progression indication. In addition, we propose redox modulation tools such as cold atmospheric plasma as a promising intervention approach against tumor cells and cancer stemness via targeting the redox homeostatic environment cells established under a pathological condition such as hypoxia. Taken together, we emphasize the central role of succinylation in bridging the gap between cellular metabolism and redox status, and its clinical relevance as a mark for cancer diagnosis as well as a target in onco-therapeutics.